2019
DOI: 10.1038/s41419-019-1964-8
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cells downregulate miR-23a-5p to activate protective autophagy in acute myeloid leukemia

Abstract: Complex molecular cross talk between stromal cells and the leukemic cells in bone marrow is known to contribute significantly towards drug-resistance. Here, we have identified the molecular events that lead to stromal cells mediated therapy-resistance in acute myeloid leukemia (AML). Our work demonstrates that stromal cells downregulate miR-23a-5p levels in leukemic cells to protect them from the chemotherapy induced apoptosis. Downregulation of miR-23a-5p in leukemic cells leads to upregulation of protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…( Ji et al, 2009 ; Li et al, 2009 ). Consistently recent studies have provided the evidence that the BM-microenvironment transfer miRNA in leukemia cells, supporting cell survival ( Liu et al, 2015 ; Ganesan et al, 2019 ).…”
Section: Msc-derived Notch and Wnt Signaling In Leukemiasupporting
confidence: 69%
“…( Ji et al, 2009 ; Li et al, 2009 ). Consistently recent studies have provided the evidence that the BM-microenvironment transfer miRNA in leukemia cells, supporting cell survival ( Liu et al, 2015 ; Ganesan et al, 2019 ).…”
Section: Msc-derived Notch and Wnt Signaling In Leukemiasupporting
confidence: 69%
“…Stromal cell-induced NF-kB signaling in leukemic cells downregulates miR-23-5p, which causes upregulation of protective autophagy via TLR2. Thus, leukemic cells are protected from chemotherapy-induced apoptosis [ 156 ]. Furthermore, it has been shown that doxorubicin treatment induced miR-21-5p expression in mesenchymal stem cells and derived exosomes.…”
Section: Combination With Cancer Therapy To Counteract Mir-mediatementioning
confidence: 99%
“…Immunofluorescence: This was done as previously reported by us (13). In summary, the myeloma cells were treated with drugs for 24 hours and cytospin slides were made.…”
Section: Co-immunoprecipitation and Immunoblots: Myeloma Cells Lines mentioning
confidence: 99%